Integration of organic supplements and inorganic nutrients levels onproductivity and profitability of maize (Zea mays) in acidic soil of Assam - JAMAKHANDI, HUCHCHAPPA; DHAR, SHIVA; RATHORE, S S; BAISHYA, LOHIT K; MANDI, SUNIL; S, SUDARSHAN; PATEL, SHASHANK; SONNAD, PRAKASH (The Indian Journal of Agricultural Sciences, 2025)
The field experiment was conducted during the rainy (kharif) season of 2023–24 to assess the impact of the integrated application of organic supplements and inorganic nutrients on maize in acidic soil. The highest grain, stover and biological yields and gross and net returns were obtained from the use of 10 t FYM/ha with 100% RDF (NPK). It was statistically similar to vermicompost @2.5 t/ha with 100% RDF (NPK) and FYM @10 t/ha with 75% RDF (NPK). This combination is also more cost-effective compared to other treatment combinations. Among organic supplements, the significantly highest PFP for N and P was obtained from the application of 10 t FYM/ha. Among inorganic nutrients levels, control recorded significantly higher PFP for N and P. Regular soil testing and the balanced use of organic and inorganic nutrients should be emphasized to optimize nutrient availability and enhance maize productivity, especially for acidic soil regions.